Discourses of destiny: a multimodal analysis of 2014 issues of Destiny Man magazine - Leopeng, Bertrand (My University, 2016)
This thesis took an interpretive approach to analysing content as presented in the print media. The focus of this study was Destiny Man magazine, a six year old lifestyle publication aimed at middle-class men in South Africa. This thesis explored how black middle-class men are presented by looking at the latent content from an interpretive stance. Therefore, a psychosocial approach was adopted to understand how political, socio-economic, and gender interact with one another at the psycho-social level. A total number of 35 articles were analysed using interpretative psychoanalytic methods and relevant critique. In addition to these 54 images were chosen to be analysed and included in an overall contextual framework relating to topics such as race, masculinity, economics, alcohol, and sport. This content was chosen from the eight 2014 issues of Destiny Man magazine. In analysis, the history of colonialism, apartheid, and the development of neoliberal capitalism was taken into account regarding how black middle class men negotiate their masculine identities in the new South Africa. The development of neoliberal capitalism and a multimodal discourse on the male psyche is explored in-depth, with the resultant social analysis. Overall, the basis of this research was to critically analyse African middle class masculinity in post-apartheid South Africa taken many factors into account. The key themes identified in the analysis include narcissism, domination, and denial of feminity, fatherhood, alcohol consumption, and performances of gender. The interactions of all of these factors have been shown to have an impact on our understanding of contemporary African middle class masculinity, affecting the construction and definition of this concept in a complex and dynamic way. Destiny Man magazine is a poignant example of how these interactions are presented in the media.
This thesis is submitted in fulfillment of the requirements for the degree of Master of Arts in Community-based Counselling Psychology in the Faculty of Humanities at the University of the Witwatersrand
Keywords: Masculinity--South Africa.; Masculinity in mass media; South Africa--Race relations; Psychoanalysis